2016
DOI: 10.1007/s00464-016-4823-z
|View full text |Cite
|
Sign up to set email alerts
|

Endoluminal vacuum therapy for gastrojejunal anastomotic leaks after Roux-en-Y gastric bypass: a pilot study in a swine model

Abstract: Endoluminal vacuum therapy is well tolerated in a swine model. GJ anastomotic leaks were consistently sealed with our device in place compared to controls. This therapy shows promise as a method to address GJ leaks in the bariatric population, and thus, we believe additional evaluation is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
0
4
0
4
Order By: Relevance
“…To comprehensively analyze the risk factors of anastomotic leak, first of all, it is emphasized that a precise and scrupulous surgical technique plays a decisive role in the healing of anastomotic tissue. Precise surgical operation needs to ensure firm and stable tissue closure, good blood supply to the stomach or other organs replacing the esophagus and targeted treatment of anastomotic tension 3–7 . At present, gastric conduit, especially the thin conduit replacing the esophagus, has been accepted by more and more surgeons.…”
Section: Complex Clinical Presentations and Possible Causes Of Anasto...mentioning
confidence: 99%
See 2 more Smart Citations
“…To comprehensively analyze the risk factors of anastomotic leak, first of all, it is emphasized that a precise and scrupulous surgical technique plays a decisive role in the healing of anastomotic tissue. Precise surgical operation needs to ensure firm and stable tissue closure, good blood supply to the stomach or other organs replacing the esophagus and targeted treatment of anastomotic tension 3–7 . At present, gastric conduit, especially the thin conduit replacing the esophagus, has been accepted by more and more surgeons.…”
Section: Complex Clinical Presentations and Possible Causes Of Anasto...mentioning
confidence: 99%
“…Compared with the control pigs, the experimental pigs treated with intraluminal vacuum were killed on the seventh day. It was observed that the defect had healed, showing outstanding therapeutic value 66 . Virgilio et al reviewed 29 research reports on EVT (ENPT) in the treatment of upper gastrointestinal anastomotic leak in 2018, comprising 209 patients with 17 retrospective studies, six prospective studies and six case reports.…”
Section: Negative Pressure and Endoluminal Vacuum Therapy (Evt E‐vat)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, all comparisons with other studies should be treated with caution, since both the measuring methods and the organs examined differed from these used in our experiment. A comparable study by Scott et al in a porcine model of anastomotic leakage after Roux-en-Y gastric bypass demonstrated that the histological specimen from EndoVAC treated pigs had lesser degree of severe inflammation and no signs of necrosis or ischemia when compared with the control group [ 45 ]. Scott et al was able to confirm these results also in a porcine model for esophagectomy [ 46 ] indirectly supporting our findings of improved tissue oxygenation upon EndoVAC therapy.…”
Section: Discussionmentioning
confidence: 99%
“…• снижение локального интерстициального отёка тканей, снижение межклеточного давления, усиление местного лимфообращения и транскапиллярного транспорта, что увеличивает скорость формирования грануляционной ткани [12];…”
Section: Discussionunclassified